Isopathic treatment effects of Arsenicum album 45x on wheat seedling growth – further reproduction trials - Lahnstein, Lisa; Binder, Mascha; Thurneysen, André; Frei-Erb, Martin; Betti, Lucietta; Peruzzi, Maurizio; Heusser, Peter; Baumgartner, Stephan (Homeopathy, 2009)
Background: Two experimental studies on wheat preintoxicated with Arsenic trioxide yielded a significant shoot growth increase after an isopathic application of Ars-alb 45x. One independent reproduction trial however, yielded an effect inversion: wheat shoot growth was significantly decreased after application of Ars-alb 45x.Aims: In this study we investigated the role of three potential confounding factors on the experimental outcome: geographical location of the experiments, influence of the main experimenter, and seed sensitivity to Arsenic poisoning. Laboratory-internal reproducibility was assessed by meta-analysis.Material and methods: Wheat poisoned with Arsenic trioxide was cultivated in vitro in either Ars-alb 45x, water 45x, or unpotentised water. Treatments were blinded and randomised. Shoot length was measured after 7 days. The stability of the experimental set-up was assessed by systematic negative control (SNC) experiments.Results: The SNC experiments did not yield significant differences between the three groups treated with unpotentised water. Thus the experimental set-up seemed to be stable. We did not observe any shoot growth increase after a treatment with Ars-alb 45x in any of the newly performed experiments. In contrast, the meta-analysis of all 17 experiments performed (including earlier experiments already published) yielded a statistically significant shoot growth decrease (−3.2%, p = 0.017) with isopathic Ars-alb 45x treatment. This effect was quantitatively similar across all five series of experiments.Conclusions: Ultramolecular Ars-alb 45x led to statistically significant specific effects in arsenic poisoned wheat when investigated by two independent working groups. Effect size and effect direction differ, however. The investigated factors (geographical location, experimenter, seed sensitivity to Arsenic poisoning) did not seem to be responsible for the effect inversion. Laboratory external reproducibility of basic research into homeopathic potentisation remains a difficult issue.
Keywords: Homeopathy; Isopathy; Ultra high dilution; Arsenic trioxide